(untitled) (Socio-economic relations in the digital society, 2019)
Changeable and unpredictable market environment, in which the private pension funds operate, increases vulnerability to internal and external negative impacts that may lead to the infringement of the financial interests of funds’ members. To prevent this scenario becoming increasingly more important the issue of financial security of non-state pension funds. The purpose of research is to improve the classifi cation of private pension funds, which will take into account the peculiarities of the fund of any kind in developing measures to ensure its financial security. Measures to ensure the fi nancial security of the private pension funds, which can be used to protect the financial interests of the fund, depends on the type of fund. In this regard it is important to systematize a plurality of types of private pension funds and fi nd out measures for ensuring financial security of each species of pension funds. In the article the approaches to the classifi cation of types of private pension funds are discussed. Author improved classifi ation of private pension funds due to the allocation of such criterions classifi cations as: organizational structure; the level of founders; isolation of fund assets from the assets of founders; attended by the founders in the distribution of fund’s income; management structure; availability to participate in the fund; form of participation in the fund; method of financing of pensions; the principle of calculating of pension benefi ts; property rights on pension assets. According to the proposed classifi cation, domestic pension funds are institutional, private, autonomous, non-profit, two-tier, voluntary, funded, savings, mutual and can be open, corporate or professional. This should be considered when developing measures to ensure the fi nancial security of the private pension funds.